Analysis of Mechanical Properties of Sandstone under Freeze-Thaw Cycles Based on Digital Image Correlation (DIC) - Daguo Quan; Shuailong Lian; Jing Bi; Chaolin Wang (Geofluids)
This paper studies the change of physical and mechanical properties of sandstone after freeze-thaw (F-T) cycle treatment. Firstly, the effects of the freeze-thaw treatment on the P-wave velocity of sandstone specimens are analyzed. It is found that the P-wave velocity decreases with the increase of the number of freeze-thaw cycles. Secondly, the effect of freeze-thaw treatment on the mechanical properties of sandstone is analyzed. The results show that the tensile strength and compressive strength of sandstone samples decrease with the increase of the number of freeze-thaw cycles. Finally, the digital image correlation (DIC) technique was used to collect the full-field deformation data of the samples, and the influence of freeze-thaw cycles on the deformation characteristics and fracture process of sandstone was analyzed. Based on the standard deviation of the principal strain in the field deformation data, the damage variables were proposed to characterize the damage process of sandstone samples in the Brazilian splitting test and the uniaxial compression test. The results show that the proposed damage variables can reflect the damage evolution process of the sample effectively. According to the variation of damage variables, the damage evolution process of sandstone specimens during the Brazilian splitting test and the uniaxial compression test can be divided into three stages: slow or negative growth stage, stable growth stage, and rapid growth stage. The research results are of great significance for predicting the failure mode and damage evolution of rock mass engineering by using digital image correlation technology.